2020
DOI: 10.1021/acssynbio.0c00146
|View full text |Cite|
|
Sign up to set email alerts
|

Pattern Engineering of Living Bacterial Colonies Using Meniscus-Driven Fluidic Channels

Abstract: Engineering spatially organized biofilms for creating adaptive and sustainable biomaterials is a forthcoming mission of synthetic biology. Existing technologies of patterning biofilm materials suffer limitations associated with the high technical barrier and the requirements of special equipment. Here we present controlled meniscus-driven fluidics, MeniFluidics; an easily implementable technique for patterning living bacterial populations. We demonstrate multiscale patterning of living-colony and biofilm forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…While a detailed analysis is yet to be done, a similar pattern has been observed in swarming B. subtilis in a meniscus open channel, named MeniFluidics [72]. Such theoretical models and experimental techniques for engineering dynamic swarming patterns could lead to the developments of active-liquid metamaterials [73] and to identify swarming bacteria in physiological conditions [72]. The latter represents a challenge since swarming is mainly observed on agar surfaces.…”
Section: Swarmmentioning
confidence: 84%
See 2 more Smart Citations
“…While a detailed analysis is yet to be done, a similar pattern has been observed in swarming B. subtilis in a meniscus open channel, named MeniFluidics [72]. Such theoretical models and experimental techniques for engineering dynamic swarming patterns could lead to the developments of active-liquid metamaterials [73] and to identify swarming bacteria in physiological conditions [72]. The latter represents a challenge since swarming is mainly observed on agar surfaces.…”
Section: Swarmmentioning
confidence: 84%
“…A theoretical model of active fluidics has suggested that the confinement geometry could result in dynamic patterns, including vortex lattices [70,71]. While a detailed analysis is yet to be done, a similar pattern has been observed in swarming B. subtilis in a meniscus open channel, named MeniFluidics [72]. Such theoretical models and experimental techniques for engineering dynamic swarming patterns could lead to the developments of active-liquid metamaterials [73] and to identify swarming bacteria in physiological conditions [72].…”
Section: Swarmmentioning
confidence: 91%
See 1 more Smart Citation
“…There are a vast number of experimental conditions which could be created to induce different spatio-temporal patterns in such microcolonies. Microfluidics has shown to be of particular help to control mechanical constraints (Ruprecht et al, 2017 ), substrate stiffness (Wang et al, 2018 ), nutrients (Alnahhas et al, 2019 ), chemical inducers (Danino et al, 2010 ), cell-cell signaling (Alnahhas et al, 2019 ), and pattern formation (Kantsler et al, 2020 ). As we showed in Figure 9 , controlling biophysical constraints using different channel layouts and mechanical properties of the substrate could produce different patterns of growth rate that give rise to structures that mimic different stages of the development of organisms (Johnson et al, 2017 ; Toda et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are a vast number of experimental conditions which could be created to induce different spatio-temporal patterns in such microcolonies. Microfluidics has shown to be of particular help to control mechanical constraints [65], substrate stiffness [66], nutrients [67], chemical inducers [13], cell-cell signaling [67] and pattern formation [68]. As we showed in figure 9, controlling biophysical constraints using different channel layouts and mechanical properties of the substrate could produce different patterns of growth rate that give rise to structures that mimic different stages of the development of organisms [25, 69].…”
Section: Discussionmentioning
confidence: 99%